Effect of extremely low‐frequency electromagnetic fields on antioxidant activity in the human keratinocyte cell line NCTC 2544. (10th October 2016) - Calcabrini, Cinzia; Mancini, Umberto; De Bellis, Roberta; Diaz, Anna Rita; Martinelli, Maddalena; Cucchiarini, Luigi; Sestili, Piero; Stocchi, Vilberto; Potenza, Lucia
Abstract: Some epidemiological studies have suggested possible associations between exposure to extremely low‐frequency electromagnetic fields (ELF‐EMFs) and various diseases. Recently, ELF‐EMF has been considered as a therapeutic agent. To support ELF‐EMF use in regenerative medicine, in particular in the treatment of skin injuries, we investigated whether significant cell damage occurs after ELF‐EMF exposure. Reactive oxygen species (ROS) production was evaluated in the human keratinocyte exposed for 1 H to 50 Hz ELF‐EMF in a range of field strengths from 0.25 to 2 G. Significant ROS increases resulted at 0.5 and 1 G and under these flux densities ROS production, glutathione content, antioxidant defense activity, and lipid peroxidation markers were assessed for different lengths of time. Analyzed parameters of antioxidant defense and membrane integrity showed a different trend at two selected magnetic fluxes, with a greater sensitivity of the cells exposed to 0.5 G, especially after 1 H. All significant alterations observed in the first 4 H of exposure reverted to controls 24 H after suggesting that under these conditions, ELF‐EMF induces a slight oxidative stress that does not overwhelm the metabolic capacity of the cells or have a cytotoxic effect.